Fatorando se a expressão a4-b4 obtém-se
Soluções para a tarefa
Respondido por
55
$
Ola
a^4 - b^4 = (a^2 + b^2)*(a^2 - b^2)
a^4 - b^4 = (a^2 + b^2)*(a + b)*(a - b)
pronto
Ola
a^4 - b^4 = (a^2 + b^2)*(a^2 - b^2)
a^4 - b^4 = (a^2 + b^2)*(a + b)*(a - b)
pronto
Respondido por
31
Vamos lá
![(a^2 + b^2)*(a^2 - b^2 ) \\ =a^4 - b^4 (a^2 + b^2)*(a^2 - b^2 ) \\ =a^4 - b^4](https://tex.z-dn.net/?f=+%28a%5E2+%2B+b%5E2%29%2A%28a%5E2+-+b%5E2+%29+%5C%5C+%3Da%5E4+-+b%5E4+)
Espero ter ajudado!
Bons estudos!
Espero ter ajudado!
Bons estudos!
Perguntas interessantes
Matemática,
1 ano atrás
Geografia,
1 ano atrás
Português,
1 ano atrás
Matemática,
1 ano atrás
Sociologia,
1 ano atrás
Matemática,
1 ano atrás